Kebiasaan makan dan status gizi pada remaja di mamuju menggunakan adolescents’ food habits checklist - Najdah, Najdah; Nurbaya, Nurbaya; Irwan, Zaki (Poltekkes Kemenkes Aceh, 2024)
Background: Adolescents's diets, which consume less fruit and vegetables and consume more fast food every day, are a global problem, including in Indonesia. Unhealthy eating patterns in adolescents contribute to increased body weight and obesity, as well as the risk of non-communicable diseases (NCDs).Objective: This study aims to determine the eating habits and nutritional status of adolescents using the adolescent food habits checklist.Method: The research was a cross-sectional study. The research was conducted at senior high schools in Mamuju Regency, West Sulawesi, from May to September 2023. The total sample of 228 students was collected using a simple random sampling technique. The data collection process uses the Adolescent food habits checklist. Respondents were interviewed directly. The data analysis was carried out univariately and displayed descriptively.Results: A total of 106 teenagers (46,5%) had healthy eating habits, but the remaining 122 teenagers (53,5%) had less healthy eating habits. Adolescents who have healthy eating habits have a lower percentage of overweight and obesity (18,9%). Meanwhile, adolescents with unhealthy eating habits had a relatively higher incidence of overweight and obesity (24,1%).Conclusion: Adolescents whose eating habits are unhealthy have a relatively high incidence of overweight and obesity compared to adolescents who have healthy eating patterns.